Gambaran Perilaku Pencegahan Penularan HIV/AIDS pada Siswa SMA Negeri 4 Kota Payakumbuh Tahun 2022 - Sri Mindayani; Amrizal Arief; Yulianita Yulianita (Jurnal Riset Hesti Medan, 2022)
HIV/AIDS in Indonesia in certain population groups (key populations) who have a high risk of HIV transmission related to their behavior. These key populations include: female sex workers (FSW), injecting drug users (IDUs), men who have sex with men (MSM), and shemale, criminals, pregnant women, Potentially Risky Men (seafarers, truck drivers, and unloading workers) and school students. The purpose of this study is to The aim of the study was to see an overview of the risky behavior of HIV/AIDS transmission in students of SMA N 4 Payakumbuh in 2022. This study was quantitative descriptive. This research is planned to be carried out in 2022 at SMAN 4 Payakumbuh. The sampling technique used is simple random sampling. The data analysis performed was univariate analysis. The results showed that most students had poor knowledge about HIV/AIDS prevention, most had low severity perceptions and most had behaviors that were not at risk of HIV/AIDS transmission. It is expected that the school needs to increase the knowledge of SMA N 4 Payakumbuh students about preventing HIV/AIDS transmission.